2012
DOI: 10.1186/1746-6148-8-60
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal biomechanics: finite element simulations of closing stroke and power stroke in equine cheek teeth

Abstract: BackgroundIn equine dentistry periodontal diseases, especially periapical inflammation, are frequently occurring problems. Anachoresis is believed to be the most common cause for the development of such disorders. Nevertheless, there is still no substantiated explanation why settlement of pathogen microorganisms occurs in equine periodontal tissues. It is expected that excessive strains and stresses occurring in the periodontal ligament (PDL) during the horse’s chewing cycle might be a predisposing factor. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…; Cordes et al . ). In young teeth, with a long reserve crown (large intra‐alveolar surface), the collagen fibres are relative loosely arranged ( Fig ).…”
Section: Structural and Functional Adaptations To Compensate For Highmentioning
confidence: 97%
“…; Cordes et al . ). In young teeth, with a long reserve crown (large intra‐alveolar surface), the collagen fibres are relative loosely arranged ( Fig ).…”
Section: Structural and Functional Adaptations To Compensate For Highmentioning
confidence: 97%
“…First, it is assumed that gingival damage occurs, leading to periodontal pocketing and microbial infection of the periodontal ligament (Cordes et al . ). Second, focal overload within the depth of the alveolus causes periodontal micronecrosis and initiates cytokine release.…”
Section: Discussionmentioning
confidence: 97%
“…Finite element simulations of the equine masticatory cycle have shown that the mechanical load within the periodontal ligament markedly increases with decreasing tooth length or increased age (Cordes et al . ).…”
Section: Treatmentmentioning
confidence: 97%
“…mastication, the horse chews at a rate of 8-10 chewing cycles per 10 s. Each cycle can place a masticatory force of 800-1000 Newtons on a premolar tooth and an even greater force on the caudal cheek teeth (Staszyk et al 2006a). Finite element simulations of the equine masticatory cycle have shown that the mechanical load within the periodontal ligament markedly increases with decreasing tooth length or increased age (Cordes et al 2012). Impacted food material is highly contaminated with potentially pathogenic micro-organisms, which have been shown to spread to the bloodstream and may also be aerosolised during the cleaning process in dogs and man (Rawlinson et al 2011).…”
mentioning
confidence: 99%